Expression and Localization of an Hsp70 Protein in the Microsporidian Encephalitozoon cuniculi - Carrie E. Jolly; Cory A. Leonard; J. Russell Hayman (International Journal of Microbiology)
Microsporidia spore surface proteins are an important, under investigated aspect of spore/host cell attachment and infection. For comparison analysis of surface proteins, we required an antibody control specific for an intracellular protein. An endoplasmic reticulum-associated heat shock protein 70 family member (Hsp70; ECU02_0100; “C1”) was chosen for further analysis. DNA encoding the C1 hsp70 was amplified, cloned and used to heterologously express the C1 Hsp70 protein, and specific antiserum was generated. Two-dimensional Western blotting analysis showed that the purified antibodies were monospecific. Immunoelectron microscopy of developing and mature E. cuniculi spores revealed that the protein localized to internal structures and not to the spore surface. In spore adherence inhibition assays, the anti-C1 antibodies did not inhibit spore adherence to host cell surfaces, whereas antibodies to a known surface adhesin (EnP1) did so. In future studies, the antibodies to the ‘C1’ Hsp70 will be used to delineate spore surface protein expression.